2006
DOI: 10.1128/aac.50.1.362-364.2006
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Action of Quinolones against a Temperature-Sensitive dnaB Replication Mutant of Escherichia coli

Abstract: Inhibition of DNA replication in an Escherichia coli dnaB-22 mutant failed to block quinolone-mediated lethality. Inhibition of protein synthesis by chloramphenicol inhibited nalidixic acid lethality and, to a lesser extent, ciprofloxacin lethality in both dnaB-22 and wild-type cells. Thus, major features of quinolone-mediated lethality do not depend on ongoing replication.Quinolones are broad-spectrum antibacterials that trap DNA gyrase and DNA topoisomerase IV on DNA as ternary complexes containing double-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…However, a reduction in ␤-lactams or in aminoglycoside antibiotic efficacy in altered microenvironments does not fully account for the observed biofilm recalcitrance toward antibiotics that are active against nongrowing bacteria, such as fluoroquinolones (61,65,66).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…However, a reduction in ␤-lactams or in aminoglycoside antibiotic efficacy in altered microenvironments does not fully account for the observed biofilm recalcitrance toward antibiotics that are active against nongrowing bacteria, such as fluoroquinolones (61,65,66).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…Sassanfar and Roberts (43) reported that SOS was not prevented after a temperature shift of a dnaC(Ts) uvrB mutant. In a direct measure of quinolone cytotoxicity, Zhao et al (58) found that temperature shift-up of a dnaB(Ts) mutant does not protect against killing by nalidixic acid or ciprofloxacin (a fluoroquinolone). In summary, while it is clear that quinolones effectively block DNA replication, the physiological consequences of this blocked replication are still uncertain.…”
mentioning
confidence: 99%
“…Rapid quinolone-mediated cell death, which does not appear to require interruption of active DNA replication fork movement (35), occurs in two ways: one that requires ongoing protein synthesis and one that does not (15). The relative contribution of each of these two lethal pathways depends on quinolone structure.…”
mentioning
confidence: 99%